Efek Abelmoschus esculentus terhadap Glukosa Darah, Superoksida Dismutase, dan Malondialdehid Rattus norvegicus Diabetes Melitus dengan Induksi Streptozotocin - Herliani, Olivia (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
In diabetes mellitus there is an increase in oxidative stress in which oxidants exceed the antioxidant system resulting from the production of oxidant-antioxidant imbalance and/or limited antioxidant defenses. Abelmoschus esculentus (âokraâ) is known as lowering blood glucose vegetable by Indonesian. A. esculentus has a high antioxidant activity that can: 1) lower H2O2 level; 2) decrease the amount of ROS; 3) lower â¢OH level. This study tried to prove that administration of A. esculentus may decrease fasting blood glucose, serum malondialdehyde, and increase superoxide dismutase activity of diabetic male white rats. This research is a pure experimental research, with randomized post test only control group designs, held in 28 days. Thirty one rats were divided into 4 groups randomly: KN = normal control group given 0.1% Na-CMC solution; KDM = DM control group injected with STZ, followed by 0.1% Na-CMC solution; P1 = treatment group 1 injected with STZ, followed by administration of A. esculentus at a dose of 775 mg/kgBW/day; P2 = treatment group 2 injected with STZ, followed by administration of A. esculentus at a dose of 1550 mg/kgBW/day. The result: administration of A. esculentus at doses of 775 mg/kgBW/day and 1550 mg/kgBW/day can not decrease fasting blood glucose and MDA serum level of diabetic male white rats. Giving A. esculentus at a dose of 1550 mg/kgBW/day may increase the activity of SOD erythrocytes of diabetic male white rats.. Conclusions: A. esculentus has the potential to lower blood glucose and MDA serum levels, also increase erythrocyte SOD activity.